Soil Characteristics of Sal Forest-chander Ecotone in South Kheri - Banerjee, S. P.; Sharma, S. D.; Gairola, S. K. (Indian Forester, 1981)
A comparative study of two sites, one representing the sal-chander and the other contiguous sal forest ecotone, was made in a part of South Kheri Forest Division, U.P. to determine the properties of the soils of the two sites, bring out the salient differences between them, and to establish hypothesis as to their origin. The study revealed that the soils of the two sites differ considerably in most of the physico-chemical properties and moisture characteristics. The soils of Chanders are of comparatively), recent origin and the grassy vegetation, perhaps the early colonizer, is the result of immaturity of the habitat possessed with unfavourable edaphic factors. Adjoining sal forest area is a habitat of mature edaphic sequence with better soil development and the invasion by sal from the periphery inwards indicates the progress of the succession form grassland to woodland.